Clinical and statistical characteristics of temporary disability cases in odontogenic inflammatory maxillofacial diseases - R. A. Saleev; A. B. Abdrashitova (Эндодонтия Today, 2019)
Research subject: temporary disability cases in patients with odontogenic inflammatory maxillofacial diseases treated in dental medical organizations for 11 years. Research objective: to study the group of odontogenic inflammatory maxillofacial diseases as a factor affecting the duration of temporary disability cases in the Republic of Tatarstan (RT) in 2007-2017. Material and methods: accounting-and-reporting forms 16-ВН, 036/у, 035/у, 043/у in dental medical organizations for the period 2007-2017. Results: the structure of odontogenic inflammatory diseases, leading to temporary disability was determined; the relationship of this group with other factors affecting the duration of temporary disability of patients was defined. Among the group of odontogenic inflammatory maxillofacial diseases, leading to the temporary disability, we identified the following nosologies: Periostitis (K10.22) – 51.6%; Exacerbation of chronic periodontitis (K04.5) – 9.6%; Acute pericoronitis (K05.2) – 8.1%; Odontogenic maxillary sinusitis (J01.0, J32.0) – 7%; Radicular cyst (K02.8) – 6.5%; Alveolitis (K10.3) – 4%; Odontogenic osteomyelitis (K10.2) – 2.4%; Lymphadenitis of mandibular nodes (L04.0) – 1%; Maxillofacial abscess (К12.2) – 1%; Polypathia – 8,8% of cases. Depending on gender, the inflammatory diseases of odontogenic origin, leading to temporary disability, are divided as follows: male patients – 42.3%, female patients – 57.7%. The greatest number of temporary disability cases associated with this group of diseases was detected in 2013, the smallest group – in 2017. At the same time, the average duration of temporary disability cases was 5.6 ± 0.08 days; it characterized by a statistically significant positive dynamics, increasing over the study period from 4.88 to 6.45 days. Conclusions: the analysis of the data obtained during the research showed statistically significant differences in the structure of temporary disability cases in odontogenic inflammatory maxillofacial diseases, depending on gender, age, seasonality and year of observation.